Dietary and anthropometric indicators of nutritional status in relation to Helicobacter pylori infection in a paediatric population - Janjetic, Mariana Andrea (2015)
It has been postulated that Helicobacter pylori infection could affect growth and appetite, consequently influencing body weight. Therefore, the association between H. pylori infection and the dietary and anthropometric indicators of nutritional status of a paediatric population were investigated. A total of 525 children (aged 4-16 years) who were referred to the gastroenterology unit of the Sor Maria Ludovica Children's Hospital from Buenos Aires, Argentina, were enrolled and completed an epidemiological questionnaire. H. pylori infection was diagnosed using the 13C-urea breath test (13C-UBT). Height and weight were assessed for calculation of anthropometric indicators. Energy and macronutrient intakes were estimated by 24 h dietary recall. Data analysis was performed using a χtest, a Student's t test, a Mann-Whitney U test and linear and logistic regressions. The prevalence of H. pylori infection was 25·1 % (with a mean age of 10·1 (sd 3·1) years). A tendency towards lower energy, carbohydrate, protein and fat intakes was observed in infected patients; however, it was not associated with H. pylori infection in any of the evaluated age groups (4-8, 9-13 and 14-16 years). Underweight, stunting, overweight and obesity were also not associated with the infection. Although height-for-age and BMI-for-age Z scores tended to be lower in infected patients, the differences between H. pylori-positive and H. pylori-negative children were not statistically significant. In conclusion, H. pylori infection was not associated with dietary intake or with anthropometric indicators in the present population of children with gastrointestinal symptoms; however, an increased sample size would be needed to confirm the observed tendency towards lower dietary intake and lower anthropometric indicators of nutritional status in H. pylori-infected children.